Whitney Interpolation Constants Bounded by 2 for k = 5, 6, 7
Let f ∈ C[0, 1], k = 5, 6, 7. We prove that if f(i/(k − 1)) = 0, i = 0, 1,..., k − 1, then \(| f(x) | 2 sup _x,x + kh [0,1] | _j = 0^k ( - 1)^j ( _j^k )f(x + jh) |.\) , number=4, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Zhelnov, O. D., year=2003, month=Apr., pages=546–549